Water pollution by plastics and microplastics: a review of technical solutions from source to sea - Nikiema, Josiane; Mateo-Sagasta, Javier; Asiedu, Zipporah; Saad, Dalia; Lamizana, B. (United Nations Environment Programme, 2020)
Plastic and microplastic pollution in aquatic environments is driven by rising global plastic production and inadequate waste management. These pollutants originate from diverse sources including microbeads, synthetic textiles, and degraded larger plastics and enter water bodies via wastewater, runoff, and sludge application. They pose physical, chemical, and biological risks, though the full extent of human health impacts remains unclear. Effective management requires interventions along the entire pollution pathway. Upstream measures include mechanical and chemical recycling, product redesign, and regulatory tools such as bans and effluent standards, supported by public awareness and incentives. In urban environments, macroplastic interception through booms, gully pots, and retention ponds helps to reduce flow into open waters. Municipal wastewater treatment plants can remove over 99% of microplastics, though most accumulate in sewage sludge, creating a secondary pollution risk. Industrial wastewater treatment, particularly in textile production, also offers targeted removal but lacks standardization. Where upstream controls are insufficient, downstream solutions like constructed wetlands, debris sweepers, and advanced filtration provide additional barriers. The report emphasizes the need for gender-sensitive approaches, noting the unequal burden on women and informal workers, and calls for context-specific, integrated strategies that align environmental goals with social equity and institutional capacity.